Mono- and Dinuclear Complexes of Tricarbonylrhenium(I) with 4-Methyl-2,2'-bipyridine-4'-carbonitrile - Mecchia Ortiz, Juan Hugo (2014)
Novel mono- and dinuclear tricarbonylrhenium(I) complexes of formula [Re(Mebpy-CN)(CO)3Cl] (1), [Re(Mebpy-CN)-(CO)3(CH3CN)](PF6) (2), and [(CH3CN)(CO)3Re(Mebpy-CN)Ru(NH3)5](PF6)3 (3), in which Mebpy-CN = 4-methyl-2,2-bipyridine-4-carbonitrile, were prepared and characterized by spectroscopic, photophysical, and computational techniques. The complete structure of complex 2 was determined by X-ray diffraction. The increased conjugation in the bipyridyl ring owing to the nitrile substituent increases the emission quantum yields of the 3MLCT (metal-to-ligand charge-transfer) lowest-lying excited states of 1 and 2 with respect to the corresponding bpy complexes (bpy = 2,2-bipyridine). The mixed-valent species of formula [(CH3CN)(CO)3Re(Mebpy-CN)Ru(NH3)5]4+ (4) was prepared in situ and as a mixed salt; the charge recombination from its metal-to-metal charge-transfer(MMCT) excited state is predicted to lie in the Marcus inverted region. The electronic structures and optical properties of all the reported complexes calculated by DFT and TD-DFT methods agree reasonably well with experimental results.